Sārasangkhēp læ datchanī singphim thāng dān watthanatham læ sātsanā kh̨̄ong Samnak Songs̄œm Sinlapawatthanatham, Mahāwitthayālai Kh̨̄on K̄æn - Sawāngčhit Sīrasā (Samnak Songs̄œm Sinlapawatthanatham, Mahāwitthayālai Kh̨̄on K̄æn, 1998)
Summaries to studies and publications on Thai customs and Buddhism at art and culture promotion unit of Khon Kaen University.